Taking the path of least resistance: a qualitative analysis of return to work or study while breastfeeding - Elaine Burns; Zoi Triandafilidis (BMC, 2019)
Abstract Background In order to meet World Health Organization recommendations for breastfeeding, many women need to combine breastfeeding with return to work or study. Barriers are often encountered when returning to work or study, which can lead to premature cessation of breastfeeding. This study aimed to explore Australian women's experiences of breastfeeding at one multi-campus university. Method This paper draws on the qualitative findings from a mixed-methods study conducted between April and November 2017. An online survey was used to explore women's experiences of breastfeeding at university. In total, 108 people participated in the survey. After the deletion of incomplete surveys, 79 staff and students survey responses were analysed. In-depth interviews were also carried out with 10 staff and students. Open text responses and in-depth interviews were analysed using thematic analysis. Results The analysis revealed four themes. The first theme, University as a positive and progressive environment for breastfeeding, explores staff and students' experiences of maternity leave, flexible work arrangements, and on-campus childcare, and their relationships with tutors, supervisors, managers and colleagues. The second theme, Finding private and safe spaces for breastfeeding, presents staff and students' experiences of using designated rooms, car parks, corridors, classrooms, and offices to breastfeed and express breast milk, and their experiences related to storage of breast milk. The third theme, Feeling self-conscious and unprofessional, reflects women's experiences of mixing their professional and personal lives, and feeling guilty for taking time out to breastfeed. The fourth theme, Developing resilience to judgement, captures women's realisation that breastfeeding on campus requires the development of a "thick skin" and the capacity to not be offended easily. Conclusions Sustaining breastfeeding requires time and commitment on behalf of the mother, as well as a supportive workplace or study environment. Transforming university campuses into breastfeeding friendly environments is long overdue and requires organisational commitment to achieve genuine reform.